Identification Of Potential Energy Harvesting Technique From KTM Railway Track - Abdul Rahman, Mohamad Hakim (Universiti Teknologi PETRONAS, 2017)
Rail transport in Malaysia comprises of heavy rail including commuter, light rapid transit (LRT), monorail, airport rail link and a funicular railway train. The railway network covers 12 states excluding Sarawak. The increasing of citizens in the country has made the traffic become crowded and people have chosen public transport as the main transport to every destination. Considering that railway track and it surrounding has higher chances to produce the sources of renewable energy, a research has been made in order to find out the energy that can be produce from various sources and the suitable device that can be used to harvest the energy. This study is crucial as harvesting electricity from the renewable energy will give a lot of contribution to the country. Besides, it also enhances the uses of green technology which purposely to reduce the pollution around the globe. This research is focusing on identification of energy harvesting on KTM railway track in Malaysia. At the end of this research, the best method of harvesting and the suitable devices to harvest potential energy from railway track will be proposed. The study will involve by doing a lot of research, the study of the costing of the device and the output produce by each devices.